The Effects of Lending Interest Rates, Inflation Rates, and Investment on Economic Growth of South East Asian Countries: economic growth of South East Asian countries during 2000-2017. - Yuliastanti, Rika; Farhan, Ali; Rahayu, Sri; Sumaryono, Roy; Kumayati, Nindya Kartika (International Journal of Scientific Research and Management (IJSRM), 2020)
This study aims to determine the effect of lending interest rates, inflation and the investment rate on economic growth in South East Asiancountries over the past seventeen years (2000-2017). This study uses a quantitative method with multiple linear regression analysis, the sample used is data from the World Bank about lending interest rates, inflation, and investment in South East Asian countries that are members of the World Bank during the period 2000-2017. From the results of multiple linear regression analysis it was found that both the lending interest rate, inflation and investment rate variables had a positive effect but unsignificant on the economic growth of South East Asian countries during 2000-2017.